Nonvalvular myocardial involvement in metastatic carcinoid disease. Issue 854 (December 1996) - Davis, G.; Birbeck, K.; Roberts, D.; Naqvi, N.
Abstract : A patient with the unusual post mortem finding of myocardial metastatic carcinoid tumour without classical valvular or endocardial carcinoid disease is described. This rare occurrence may represent an aggressive type of carcinoid tumour, with metastatic disease occurring before the development of classical fibrous valvular and endocardial pathology.